Knowledge management in theory and practice - Dalkir, Kimiz (MIT Press, 2017)
The ability to manage knowledge has become increasingly important in today's knowledge economy. Knowledge is considered a valuable commodity, embedded in products and in the tacit knowledge of highly mobile individual employees. Knowledge management (KM) represents a deliberate and systematic approach to cultivating and sharing an organization's knowledge base. This textbook and professional reference offers a comprehensive overview of the field. Drawing on ideas, tools, and techniques from such disciplines as sociology, cognitive science, organizational behavior, and information science, it describes KM theory and practice at the individual, community, and organizational levels. Chapters cover such topics as tacit and explicit knowledge, theoretical modeling of KM, the KM cycle from knowledge capture to knowledge use, KM tools, KM assessment, and KM professionals. This third edition has been completely revised and updated to reflect advances in the dynamic and emerging field of KM. The specific changes include extended treatment of tacit knowledge; integration of such newer technologies as social media, visualization, mobile technologies, and crowdsourcing; a new chapter on knowledge continuity, with key criteria for identifying knowledge at risk; material on how to identify, document, validate, share, and implement lessons learned and best practices; the addition of new categories of KM jobs; and a new emphasis on the role of KM in innovation. Supplementary materials for instructors are available online.